Sarcopenia, ingesta de nutrientes y estado nutricional de residentes del centro de atención para personas adultas mayores "San Francisco de Asís”, Iquitos 2024 - Hidalgo Piña, Mirian (2024)
The objective of this research was to evaluate the relationship between sarcopenia, nutrient intake and nutritional status of older adults residing in the ‘San Francisco de Asis’ Care Centre for Older Adults in Iquitos, Peru in 2024. The study was a descriptive non-experimental study, using a cross-sectional and correlational design. The study sample consisted of 30 older adults, who were evaluated by means of anthropometric measurements, dynamometry and direct weighing of food. Indicators such as BMI, abdominal perimeter, muscle strength and skeletal muscle mass index (SMMI) were analysed. The results showed that 33.3 % of females and 13.4 % of males had a normal nutritional status. Thinness was found in 33.3 % of males and 10.0 % of females. Only males with values of 6.7 % and 3.3 % were overweight and obese, respectively. 50% of males and 43.3% of females showed probable sarcopenia. In terms of macronutrient intake, older adults consumed 62.29 % of carbohydrates, 13.21 % of proteins and 28.57 % of lipids. In terms of micronutrients, there was an average intake of calcium (359.45 mg), phosphorus (796.94 mg) and vitamin A (59.631 µg), showing that the diet was deficient in several micronutrients essential for muscle health. Sarcopenia showed significant assessment with nutrient intake, especially protein, and with nutritional status indicators such as BMI, muscle strength and IMME. These findings highlight the need for nutritional interventions focused on improving protein intake and strengthening muscle health in older adults.